2020
DOI: 10.26508/lsa.201900618
|View full text |Cite
|
Sign up to set email alerts
|

SARM1 deficiency promotes rod and cone photoreceptor cell survival in a model of retinal degeneration

Abstract: Retinal degeneration is the leading cause of incurable blindness worldwide and is characterised by progressive loss of light-sensing photoreceptors in the neural retina. SARM1 is known for its role in axonal degeneration, but a role for SARM1 in photoreceptor cell degeneration has not been reported. SARM1 is known to mediate neuronal cell degeneration through depletion of essential metabolite NAD and induction of energy crisis. Here, we demonstrate that SARM1 is expressed in photoreceptors, and using retinal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…As NAD + loss is a common pathology of many retinal diseases, this raises the possibility that SARM1 activation may contribute to a wide range of retinal disorders. In support of this conjecture, recent studies found that SARM1 promotes retinal degeneration in X-linked retinoschisis 62 and rhodopsin-deficient mice 63 .…”
Section: Discussionmentioning
confidence: 79%
“…As NAD + loss is a common pathology of many retinal diseases, this raises the possibility that SARM1 activation may contribute to a wide range of retinal disorders. In support of this conjecture, recent studies found that SARM1 promotes retinal degeneration in X-linked retinoschisis 62 and rhodopsin-deficient mice 63 .…”
Section: Discussionmentioning
confidence: 79%
“…As NAD + loss is a common pathology of many retinal diseases, this raises the possibility that SARM1 activation may contribute to a wide range of retinal disorders. In support of this conjecture, recent studies found that SARM1 promotes retinal degeneration in X-linked retinoschisis ( Molday et al, 2007 ) and rhodopsin-deficient mice ( Ozaki et al, 2020 ).…”
Section: Discussionmentioning
confidence: 81%
“…Subsequently, studies have demonstrated that SARM1 is also a key part of a highly conserved axonal death pathway that is activated by nerve injury ( Gerdts et al, 2013 ; Osterloh et al, 2012 ). Notably, SARM1 deficiency confers protection against axonal degeneration in several models of neurodegenerative conditions ( Kim et al, 2007 ; Ko et al, 2020 ; Ozaki et al, 2020 ; Uccellini et al, 2020 ), making SARM1 a compelling drug target to protect axons in a variety of axonopathies ( Krauss et al, 2020 ; Loring et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%